2004
DOI: 10.1590/s1806-83242004000400012
|View full text |Cite
|
Sign up to set email alerts
|

CT-based analysis of malignant tumor volume and localization: a preliminary study

Abstract: ABSTRACT:The purpose of this study was to correlate 3D-CT (3D computed tomography) volume measurements of malignant tumors with the response to treatment, and to observe bone invasion in these lesions applying a specific imaging protocol. We analyzed 17 individuals with maxillofacial malignant lesions who were submitted to spiral CT (2D-CT). The original data were transferred to an independent workstation using a 3D volume rendering package software, which was used by two examiners to obtain area and volume me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…[21][22][23] stated that for detailed evaluation of the mandible it is essential to obtain CT scans with bone windows and narrow cuts, and the accuracy found in his work was 68%. According to Baxter and Sorenson 21 , identification of the number of lesions was inaccurate when the diameter was comparable to or less than the CT slice thickness, not allowing a correct identification of bone lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] stated that for detailed evaluation of the mandible it is essential to obtain CT scans with bone windows and narrow cuts, and the accuracy found in his work was 68%. According to Baxter and Sorenson 21 , identification of the number of lesions was inaccurate when the diameter was comparable to or less than the CT slice thickness, not allowing a correct identification of bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Baxter and Sorenson 21 , identification of the number of lesions was inaccurate when the diameter was comparable to or less than the CT slice thickness, not allowing a correct identification of bone lesions. Furthermore, Cavalcanti et al 22 demonstrated high false positive and false negative rates when determining mandibular bone invasion using 3-mm-thick axial slices. In the present work, using a 0.5 mm slice thickness with a thinner interval of reconstruction (0.3 mm) for MSCT and 0.25 mm voxel size for CBCT, 90.4% and 90.7% of sensitivity and 96.3% and 95.9% of specificity (median values) were found regarding the number of simulated lesions respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have discussed the importance of acquisition parameters as slice thickness in bone lesion evaluation 4,9,26 . Shaha 26 stated that for detailed evaluation of the mandible is essential to obtain the CT scans with bone windows and narrow cuts, since the accuracy found in his work was 68%, using a singleslice CT.…”
Section: Discussionmentioning
confidence: 99%
“…According to Baxter and Sorenson 4 , the number of lesions is inaccurate when the diameter is comparable to or less than the CT slice thickness 12 . Furthermore, Cavalcanti, et al 9 demonstrated a high false positive and false negative rates when determining bone invasion in mandible, because 3-mm-thick axial slices are used, and also most authors suggested that thin slices are needed to detect more bone details 4,9,26 .…”
Section: Discussionmentioning
confidence: 99%
“…After complete selection of the area of interest (in all the axial images), the 3D reconstruction was used for final visualisation of the anatomical structures ( Fig. 6), following the methodology used in previous studies 3,4,17 .…”
Section: Methodsmentioning
confidence: 99%